Different signalling in infarcted and non-infarcted areas of rat failing hearts: A role of necroptosis and inflammation - Lichý, Martin; Szobi, Adrián; Hrdlička, Jaroslav; Horváth, Csaba; Kormanová, Veronika; Rajtík, Tomáš; Neckář, Jan; Kolář, František; Adameová, Adriana (Journal of cellular and molecular medicine, 2019)
Necroptosis has been recognized in heart failure (HF). In this study, we investigated detailed necroptotic signalling in infarcted and non-infarcted areas separately and its mechanistic link with main features of HF. Post-infarction HF in rats was induced by left coronary occlusion (60 minutes) followed by 42-day reperfusion. Heart function was assessed echocardiographically. Molecular signalling and proposed mechanisms (oxidative stress, collagen deposition and inflammation) were investigated in whole hearts and in subcellular fractions when appropriate. In post-infarction failing hearts, TNF and pSer229-RIP3 levels were comparably increased in both infarcted and non-infarcted areas. Its cytotoxic downstream molecule p-MLKL, indicating necroptosis execution, was detected in infarcted area. In non-infarcted area, despite increased pSer229-RIP3, p-MLKL was present in neither whole cells nor the cell membrane known to be associated with necroptosis execution. Likewise, increased membrane lipoperoxidation and NOX2 levels unlikely promoted pro-necroptotic environment in non-infarcted area. Collagen deposition and the inflammatory csp-1-IL-1β axis were active in both areas of failing hearts, while being more pronounced in infarcted tissue. Although apoptotic proteins were differently expressed in infarcted and non-infarcted tissue, apoptosis was found to play an insignificant role. p-MLKL-driven necroptosis and inflammation while inflammation only (without necroptotic cell death) seem to underlie fibrotic healing and progressive injury in infarcted and non-infarcted areas of failing hearts, respectively. Upregulation of pSer229-RIP3 in both HF areas suggests that this kinase, associated with both necroptosis and inflammation, is likely to play a dual role in HF progression.
Keywords: Apoptosis; Cell Death; kardiomyocyty; Oxidative Stress; srdeční selhání; Necroptosis; Necrosis; signální transdukce; zvířata; Signal Transduction; potkani Sprague-Dawley; Heart Failure; zánět; Animals; Receptor-Interacting Protein Serine-Threonine Kinases; Inflammation; nekróza; Up-Regulation; buněčná smrt; nekroptóza; apoptóza; upregulace; infarkt myokardu; Rats; Male; Myocardial Infarction; oxidační stres; mužské pohlaví; Rats, Sprague-Dawley; krysa rodu Rattus; serin-threoninkinasy interagující s receptory; Myocytes, Cardiac